Soigner des femmes en couches : un interdit levé pour évangéliser ? - Anne Jusseaume (Chrétiens et Sociétés, 2013)
Nuns do not traditionally care for pregnant women and women who have just given birth, whether it be at home or at the hospital. However, the Petites Soeurs de l’Assomption, a congregation that cared for the urban poor in their homes, did take care of women before and after birth. Alongside midwives and philanthropic women, they formed part of the feminine entourage that surrounded women during labour. They were concerned with the hygiene of the mother and newborn, took care of the home while the mother was confined to bed, and brought material support to the families. Their activities, specifically aimed at the urban poor, formed part of the political and feminist debates of the Third Republic. Their work fit into the government’s hygienist and maternalist policies, which aimed to fight French population decline and sought to moralize the working class. At the same time that welfare services were being secularised, the sisters committed themselves to the care of popular pregnancy and birth, and tried to fight against dechristianization by encouraging the poor to take the sacraments. Through a local case study of the quartier de Grenelle in Paris, this piece examines different aspects of care that could be given to pregnant women and mothers under the Third Republic.